2009
DOI: 10.1097/nen.0b013e3181a19a5a
|View full text |Cite
|
Sign up to set email alerts
|

Demyelination, Inflammation, and Neurodegeneration in Multiple Sclerosis Deep Gray Matter

Abstract: Gray matter (GM) lesions are recognized as important components of the pathology of multiple sclerosis (MS), and involvement of the deep gray matter (DGM) is suggested by magnetic resonance imaging. The aims of this study were to determine the frequency and distribution of lesions and characterize the inflammatory and neurodegenerative changes in DGM of MS patients. Histochemistry, immunohistochemistry, and morphometry were performed on whole coronal sections of 14 MS and 12 control (6 normal, 6 from amyotroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
249
1
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(278 citation statements)
references
References 47 publications
18
249
1
5
Order By: Relevance
“…In addition, the connections to and from several deep nuclei such as the globus pallidus, caudate, and amygdala, were also discriminating between patients and controls. Early and frequent lesions in the thalamus and caudate as well as in the putamen, globus pallidus, or amygdalae have been recently pointed out (Vercellino et al, 2009), and these regions exhibit a rapid atrophy following the first clinical event (Audoin et al, 2010). Deep gray matter regions (caudate, lentiform) have also been reported as discriminative using multivariate predictive modelling on structural T2-weighted data (Weygandt et al, 2011).…”
Section: Altered Connectivity and Grey Matter Changesmentioning
confidence: 99%
“…In addition, the connections to and from several deep nuclei such as the globus pallidus, caudate, and amygdala, were also discriminating between patients and controls. Early and frequent lesions in the thalamus and caudate as well as in the putamen, globus pallidus, or amygdalae have been recently pointed out (Vercellino et al, 2009), and these regions exhibit a rapid atrophy following the first clinical event (Audoin et al, 2010). Deep gray matter regions (caudate, lentiform) have also been reported as discriminative using multivariate predictive modelling on structural T2-weighted data (Weygandt et al, 2011).…”
Section: Altered Connectivity and Grey Matter Changesmentioning
confidence: 99%
“…Thus, the role of individual GM compartments (eg, cortical and deep GM) in predicting disability worsening remains to be established. Among brain GM structures, several pathologic 13,14 and imaging [15][16][17][18][19] studies have demonstrated consistently that thalamic involvement is, from the earliest stages of the disease, a prominent feature of MS. [20][21][22][23] In a longitudinal DTI study of a relatively large cohort of patients with PPMS with a clinical follow-up of approximately 5 years, 11 we found that baseline GM average MD of the whole brain and baseline EDSS scores 24 were independent predictors of subsequent clinical deterioration during the study period. Against this background, the objective of this study was to determine the relative contribution of baseline damage to the thalamus (in terms of focal lesions, atrophy, and DTI abnormalities) as well as its change during a 15-month period in predicting the accumulation of disability during the subsequent 5 years in this cohort of patients.…”
mentioning
confidence: 99%
“…In very recent histochemistry, immunohistochemistry, and morphometry research performed on whole coronal sections of 14 MS brains, deep gray matter demyelinating lesions were detected most often in the thalamus (11/14) and caudate (9/ 14), while hypothalamus involvement was only 4/14, and a preponderance of activated microglia were found in these lesions in the postmortem series of cases. 7 Because ferritin can be used as an activation marker of microglia and reflects the extent of inflammation in brain, 8 we presumed that microglia activation may exist in the hypothalamus and that elevated serum ferritin might be found in our patient. In agreement with our hypothesis, an increased serum ferritin level was found, which represented active inflammation with ongoing oxidative damage.…”
Section: Discussionmentioning
confidence: 99%